Consumer Perceptions of Green Supply Chain Management and Electric Vehicles Purchasing Intentions : A Roadmap to Achieving Sustainable Goals - Singh, Mannat; Dahiya, Rekha (Indian Journal of Marketing, 2026)
Purpose : This research examined the impact of consumers’ perceptions of green supply chain management (GSCM) practices on their intention to purchase electric vehicles (EVs) in India, emphasizing the mediating role of perceived product performance. Methodology : The study purposively selected 223 respondents who were environmentally conscious and well aware of the EV sector developments. A quantitative methodology was employed, wherein a structured questionnaire was used to collect the data. The data was analyzed using covariance-based SEM (CB-SEM). Findings : Consumer perceptions of green supply chain practices significantly and positively influenced both perceived product performance and purchase intentions. Perceived product performance had a direct correlation to the purchasing intention prediction. Sustainable logistics significantly impacted the potential customers’ perception of green supply performance, along with responsible customer management. The most significant predictors of perceived performance turned out to be energy efficiency and reliability of the product. Practical Implications : Automobile makers must focus on showcasing and marketing midstream as well as downstream green supply chain practices, and also focus on the reliability and efficiency of their products in marketing communications. This gives us a roadmap for policymakers who should emphasize on promotion of standardized disclosures of company environmental policies and practices and should also incentivize life-cycle sustainable practices to give a boost to the EV sector. Originality : This study bridged the gap between supply-side sustainability practices and demand-side behavior by linking green supply chain practices to purchasing intentions and identified perceived product performance as a key mediator.